Konsep Pendidikan Tauhid: Pandangan Al-Qur'an - Fahrur Rozy; Tri Abdi Syahputra; Asnil Aidah Ritonga; Mohammad Al Farabi (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Education is the most important element in life. Quality education brings good influence, and vice versa. The success of a civilisation is certainly influenced by education. According to the Islamic perspective, monotheism is the most important basis in the formation of human character and personality. Tawhid education has an influence on humans in understanding the direction of the purpose of this life. In this modern era, many humans are unclear about the direction of their life goals. This study aims to interpret the verses of the Qur'an related to monotheism education. The technique used in collecting data in this study uses library research sourced from journals, scientific papers, books and books of tafsir. In addition, as for the results of this study, namely tawhid education is needed in everyday life, to overcome the problems of faith that are rampant today. In the Qur'an, there are many references to tawhid education, such as the Qur'anic verses that the author discusses, namely Q.S. Al-Isra verse 36, Q.S. Al-Baqarah verse 284, and Q.S. yunus verse 61